A cephalometric treatment evaluation of class II division 1 malocclusion treated with multiloop edgewise archwire (MEAW) therapy - Serraon, Maria Laarni P.
The purpose of the study is to retrospectively evaluate the treatment effects of MEAW therapy on the skeletal, dental, and soft tissue changes of class II Div. I malocclusions. Records of thirty-seven samples were collected with records of cephalograms pre-treatment (T1), immediately after treatment (T2), and retention (T3). The samples consisted of twenty-two males and fifteen females with a mean age of 12.2 years at the start of treatment, 15.2 years at the end of treatment and 17.8 years at retention. Orthopedic and orthodontic changes were evaluated cephalometrically. The mean changes after treatment and retention were subjected to statistical analysis using Student's paired t-test. The level of significance was set at p0.001.There was no significant effect on the maxilla but there was a significant growth of the mandible. There was reduction in ANB angle of 1.3?, AB to MP of 3.4?, and angle of convexity of 1.8?. There were no significant changes in the mandibular plane angle, Y-axis and gonial angle. There was significant extrusion and retroclination of the upper incisors while the lower incisors proclined. The upper and lower molars extruded and uprighted. The lower molars had a significant mesial movement of 3mm. The overjet was reduced by mm and the overbite decreased 3.6 mm. Both anterior and posterior facial heights increased by 5.1 mm abd 4.4 mm respectively. The class II correction was achieved through differential growth of the maxilla and the mandible. The 3 mm. mesial movement of the lower molars corrected the class II molar relationship.Twenty-six out of the thirty-seven samples had retention cephalograms and they were used to assess the stability three years out of retention. Post retention changes showed that there was post treatment growth of the mandible resulting to increase in the posterior facial height 3.2 mm, increase in Y-axis of .9? and decrease in gonial angle of 2.2?. The upper and lower incisors extruded contributing to the relapse of the overbite of 2.1 mm. The lower incisors retrocline by 2.7?. This resulted to the relapse of the overjet by 1.1 mm.The Multi-loop edgewise archwire technique as a treatment modality can effectively correct class II div. 1 malocclusion, The correction attained after treatment tends to remain stable. However, relapse noted on the overjet and overbite are related to the post treatment extrusion of the incisors and their tendency to revert back to its pre-treatment axial inclination.